THE EFFECT OF CAPITAL STRUCTURE, FIXED ASSET INTENSITY AND COMPANY SIZE ON CORPORATE INCOME TAX PAYABLE - Siti Khurotul Aini; Dwi Septiani (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the influence of capital structure, fixed asset intensity, and company size on corporate income tax payable in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2023 period. The method used is a quantitative method with secondary data from the financial statements of consumer non-cyclicals sector companies listed on the IDX in the period. This study applied a purposive sampling technique, which resulted in 31 companies over six years with a total of 186 observations. The data was analyzed using EViews 12 software. The results of the study show that: (1) Capital structure, fixed asset intensity, and company size simultaneously affect the income tax of payable entities; (2) Capital structure affects the income tax of the payable entity; (3) The intensity of fixed assets has no effect on the income tax of the payable entity; (4) The size of the company affects the income tax of the payable entity.